Manipulation of safed musli (Chlorophytum borivilianum) tubers using growth regulator to enhance sprouting and storability - Jaafar, Juju Nakasha (2012)
Establishing a new crop outside its origin is a challenge in the agriculture production. Understanding the behavior of planting materials as well as the plant growth and development under specific conditions are important in cultivating a new crop. Therefore, this thesis focuses on three aspects of handling the planting materials of safed musli, a newly introduced crop in Malaysia. In the first experiment, safed musli tuber were soaked gibberellic acid (GA3)at 10, 15 and 20 mg/L, and humic acid (HA) at 5, 10 and 15% to break tuber dormancy. Result from this experiment showed that both GA3 and HA were successful in breaking the tuber dormancy and promoted homogenous sprouting. Tubers treated with 20 mg/L GA3 and 15% HA were found to have higher leaf area index, fibrous root length, and higher number of tubers with bigger tuber diameter which finally translated to increased yield. However,15% HA was more cost effective compared to 20 mg/L GA3. In the second experiment, tubers were either planted as whole or cut with three levels of tuber weight (3, 6 and 9 g). There was no interaction between the two factors all measured parameters. Besides, different tuber weight categories did not affect the plant growth. However, when the tubers were subjected to cutting, it influenced the plants to produce higher leaf area index, fibrous root length, higher number of tubers, bigger tuber diameter and finally, higher tuber dry weight. In the third experiment, tubers were stored in two temperatures which is at 28˚C and 10˚C and were sprayed with paclobutrazol at four concentrations of 0, 100, 200 and 300 mg/L. The data demonstrated that safed musli tubers had excessive sprouting in 28˚C especially for treatment without paclobutrazol. Paclobutrazol at 28˚C was not successful in inhibiting sprouting, but it reduced sprouting as well as sprout growth. Only minimal sprouting occurred in tubers stored at 10˚C during the eight months of storage. Upon removal from the storage environment, the tuber viability was also not affected by this low temperature. Overall, in order to cultivate safed musli, cut tuber weighing 3 g should be treated with 15% HA for an hour prior to planting. Upon harvest the tubers can be stored up to five months at 10°C without loss in planting quality.